Design printed circuit board for single-input dual-output flyback converter - Chen, Haoran (2018)
In the electrical industry, the demand of flyback converters has been on the rise due to its advantages of small size and galvanic isolation. To further enhance the cost effectiveness of the flyback converter, we propose a single-input dual-output flyback converter. It contributes to further reduce cost, volume and weight because two output windings share one transformer core. The choice of which branch is operated is determined by two switches connected with the two secondary windings. All the switches in this circuit are MOSFETs made by silicon carbide. This kind of MOSFET can be operated at high switching frequency. The purpose of this report is to 1) select appropriate devices which will be used in the flyback converter circuit based on certain design guidelines, 2) design the schematics and PCBs of for both the main power circuit and sensor circuit with signal conditioning. In view of the fact that most components are not available in the original design library of the commercial software Altium Designer, the schematic and package of these components should be designed and added to the integrated library. The information about size and shape of the package can be obtained from dimension section of datasheet. The schematic and the PCB of the circuit is designed on a software which name is Altium Designer. In this software, the schematic and package of devices can be designed and added to the library. In the schematic design, these schematic can be picked from the library and added to circuit schematic directly. Then, the PCB of this circuit can be produced automatically according to the schematic. The final step is to design the layout of this circuit and place wires. All those steps can be implemented using Altium Designer software.